Unsymmetrically Chlorinated Non‐Fused Electron Acceptor Leads to High‐Efficiency and Stable Organic Solar Cells - Ma, De‐Li; Zhang, Qian‐Qian; Li, Chang‐Zhi (Angewandte Chemie International Edition, 2023)
Searching the cost‐effective organic semiconductors is strongly needed in order to facilitate the practice of organic solar cells (OSCs), yet to be fulfilled. Herein, we have succeeded in developing two non‐fused ring electron acceptors (NFREAs), leading to the highest efficiency of 16.2 % for the NFREA derived OSCs. These OSCs exhibit the superior operational stabilities under one sun equivalent illumination without ultraviolet (UV) filtration. It is revealed that the modulation of halogen substituents on aromatic side chains, as the new structural tool to tune the intermolecular interaction and optoelectronic properties of acceptors, not only promotes the interlocked tic‐tac‐toe frame of three‐dimensional stacks in solid, but also improves charge dynamics of acceptors to enable high‐performance and stable OSCs. Two non‐fused ring electron acceptors (NFREAs) have been developed. The halogen substituents on the aromatic side chains, as the new structure design tools, not only facilitate the construction of 3D stacks in solid, but also optimize the optoelectronic properties of the NFREAs, leading to organic solar cells with 16.2 % efficiency and excellent operational stability.